15 Years collaboration between SSTC NRS (Ukraine) and ISTec (GRS) in NPP I&C area - Schnuerer, G.; Yastrebenetsky, M. (Ядерна та радіаційна безпека, 2010)
Collaboration between the Institute for Safety Technology (ISTec) from Germany and the
State Scientific Technical Center on Nuclear and Radiation Safety (SSTC NRS) from Ukraine
has been performed for about 15 years. The main topics of cooperation have been assessment
and qualification of digital safety I&C systems for NPP, licensing of those systems and
elaboration of standards and guidelines for the licensing processes mentioned above. The
paper gives a brief overview about the activities and results of the collaboration. Співпраця Інституту технологій безпеки (Німеччина) та Державного науково-
технічного центру з ядерної та радіаційної безпеки (Україна) триває протягом 15
років. Основними напряма-ми співпраці є оцінка і кваліфікація цифрових інформаційних
та ке-руючих систем АЕС, ліцензування цих систем і розробка стандартів та
керівництв для ліцензування. Стаття містить короткий огляд цієї діяльності та її
результатів. Сотрудничество Института технологий безопасности (Германия) и
Государственного научно-технического центра по ядерной и радиационной безопасности
(Украина) продолжается в течение 15 лет. Основными направлениями сотрудничества
являются оценка и квалификация цифровых информационных и управляющих систем
АЭС, лицензирование этих систем и разработка стандартов и руководств для
лицензирования. Статья содержит краткий обзор этой деятельности и ее
результатов.